GROWTH AND SURVIVAL RATE OF TIGER SHRIMP (Penaeus monodon) WITH DIFFERENT FEEDING FREQUENCY - Romadon Dongoran; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in January-February 2015, at Ujung Batee fisheries Brackish Water Cultivation Hall, Nanggroe Aceh Darussalam Province. The aim of this study was to determine the effect of different feeding frequency on the growth and survival rate of tiger shrimp (Penaeus monodon). The research method used an experimental with 3 treatments and 3 replications of feeding 2 times a day (P1); feeding 3 times a day (P2) and feeding 4 times a day (P3). Data were analyzed using ANOVA (P< 0,05). 180 tiger shrimp tails were reared in 9 “toples” with aeration (25L). The results showed feeding 4 times a day gave a higher growth of weight gain (2,896 g), daily growth rate (8,24%), the growth of length (13,29 mm), and survival rate (80%).Keyword : tiger shrimp, feeding frequency, and growth